2007
DOI: 10.1016/j.cell.2007.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Single-Molecule Studies Reveal Dynamics of DNA Unwinding by the Ring-Shaped T7 Helicase

Abstract: Helicases are molecular motors that separate DNA strands for efficient replication of genomes. We probed the kinetics of individual ring-shaped T7 helicase molecules as they unwound double-stranded DNA (dsDNA) or translocated on single-stranded DNA (ssDNA). A distinctive DNA sequence dependence was observed in the unwinding rate that correlated with the local DNA unzipping energy landscape. The unwinding rate increased approximately 10-fold (approaching the ssDNA translocation rate) when a destabilizing force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
282
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 226 publications
(306 citation statements)
references
References 57 publications
19
282
5
Order By: Relevance
“…As shown in Fig. 3b, before encountering the nucleosome, the helicase unwound the dsDNA at the expected rate, as reported previously [28][29][30][31][32] . On encountering the nucleosome, the helicase showed a discrete pause, consistent with previous studies that characterized nucleosomes as major barriers for helicase unwinding 33 .…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…As shown in Fig. 3b, before encountering the nucleosome, the helicase unwound the dsDNA at the expected rate, as reported previously [28][29][30][31][32] . On encountering the nucleosome, the helicase showed a discrete pause, consistent with previous studies that characterized nucleosomes as major barriers for helicase unwinding 33 .…”
Section: Resultssupporting
confidence: 51%
“…DNA tethers were formed in flow chambers and were unzipped using an optical trap with a loading rate clamp of 10 pN s À 1 ( Fig. 1 and Supplementary Figs 3 and 5) through the bound protein [10][11][12]15,16,[28][29][30][31]55,[57][58][59][60] . Briefly, chambers were first incubated with antidigoxygenin at 0.2 mg ml À 1 for 5 min, and then the surface was blocked by incubation with casein at 5 mg ml À 1 for 5 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…65 One recent study used this DNA unzipping configuration to study the DNA unwinding activity of the ring-shaped T7 helicase, and revealed that the helicase functioned through a mechanism involving protein induced separation of the DNA strands. 39 Optical tweezers can also measure the forces exerted by molecules. For example, the first studies that measured the forces produced by a transcribing molecule of RNA polymerase relied upon optical tweezers.…”
Section: Optical Tweezers (Ot)mentioning
confidence: 99%
“…[23][24][25][26] Single-molecule methods have also been used to examine other nucleic acid motors like bacteriophage lambda exonuclease, 27,28 DNA polymerases, [29][30][31][32] Rad54 and Rdh54 DNA translocases, [33][34][35] the chromatin remodeling complexes RSC and Swi/Snf, 36,37 and several different helicases. [38][39][40] A large volume of work has also focused on the conformational dynamics and physical properties of single molecules including the folding, unfolding and strain response of proteins, DNA, and RNA. [41][42][43][44][45][46][47][48] This review is written for the nonspecialist who may be interested in understanding or pursuing single-molecule experiments.…”
Section: Introductionmentioning
confidence: 99%